Integrated digital technology to enhance student teacher’s 4Cs through photovoice dialogue: From camera to classroom - Srieng, Kimsron; Sam, Chanphirun; Mustafa, Zainun (CV. Yudhistt Fateeh, 2025)
Integrating digital technology into classroom has modernized the ways of teaching, providing new chances for the students’ efficiency engagement and reflective learning with critical thinking skills. This study aims to investigate student teacher’s experience and 4Cs from implementing photovoice dialogue. The study employed a quantitative research design, one-group posttest experimental approach, with 198 student teachers who joined a field trip performing photovoice dialogue activities. Throughout the research, the student teachers applied digital photography to document and shared different educational topics, navigated by classroom discussions which fostered deeper analysis of main concepts. The data were collected; using a 4-point Likert scale assessment measuring the student teachers' learning experiences and satisfaction reflection of photovoice dialogue implementation. The data were then analyzed using SPSS software with descriptive statistics such as mean, standard deviation. The results showed that the student teachers have good experience with photovoice dialogue such personal growth and useful learning activities. They also improve critical thinking, creativities, communication and collaboration skill throughout practicing this approach. It braces teachers in pre-service program to turn into not only greater confident teachers but also introspective practitioners qualified of enhancing critical thinking and community involvement in their future classes.